Promoting Spiritual Health: Using Poetry as a Coping Strategy for Iranian Women Post-divorce - Zarei, Fatemeh (Arts and Health Promotion: Tools and Bridges for Practice, Research, and Social Transformation, 2021)
Iranian women who experience divorce are dealing with a complex life event with significant social and psychological impacts. Recommended coping strategies often include stress management, relaxation methods, yoga, and meditation. Unfortunately, these strategies fail to address the wider gender and cultural context that affects the experience of divorce for women in Iran. Because of the financial, social, and cultural complexity of divorce, strategies beyond psychological techniques are needed for coping with the consequences of divorce. This chapter explores the use of poetry as a literary art form to promote meaning-making and social support for Iranian women post-divorce through a series of 15 one-hour poetry reading, interpretation, and discussion sessions. The poetry of Rumi, the revered Iranian poet, was shared to prompt conversation that included discussions of mystical, existential, and universal philosophical concepts. The intention of the program was to stimulate a dialogue about coping strategies for life post-divorce through the explanation and interpretation of concepts explored in the verses. The women identified and acknowledged difficulties they experienced while building a sense of belonging. Based on observations and their self-expression, the program supported meaning-making from post-divorce suffering and the participants reported experiencing a greater sense of peace, tranquility, and well-being, and an openness to envisioning a purpose for their future.